Performance metrics for Multi-Input Multi-Output (MIMO) visible light communications - Tran, T; O'Brien, D (2012)
This paper reports a study of different metrics to measure the performance of different MIMO Optical Wireless geometries. Signal to Interference Noise Ratio (SINR) is found to be the most appropriate metric of those studied. The reported simulation results also illustrate that overall system performance can be approximated to that of the worst MIMO sub-channel. © 2012 IEEE.